2021
DOI: 10.3390/jcm10235495
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Refractory Epilepsy in Patients with Tuberous Sclerosis Complex: A Systematic Review

Abstract: Background: Epilepsy affects 70–90% of patients with tuberous sclerosis complex (TSC). In one-third of them, the seizures become refractory to treatment. Drug-resistant epilepsy (DRE) carries a significant educational, social, cognitive, and economic burden. Therefore, determining risk factors that increase the odds of refractory seizures is needed. We reviewed current data on risk factors associated with DRE in patients with tuberous sclerosis. Methods: The review was performed according to the PRISMA guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…However, recent studies have shown that the use of mTOR inhibitors, such as rapamycin or everolimus, can provide promising results for more than one of the affected systems. 5 , 7 , 9 The patient's management was based on the symptoms during her hospital stay and treatment for seizure control was continued upon discharge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent studies have shown that the use of mTOR inhibitors, such as rapamycin or everolimus, can provide promising results for more than one of the affected systems. 5 , 7 , 9 The patient's management was based on the symptoms during her hospital stay and treatment for seizure control was continued upon discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Vigabatrin is considered as the first‐line treatment for epileptic spasms, while surgery or vagal stimulation can also be considered as treatment options. However, recent studies have shown that the use of mTOR inhibitors, such as rapamycin or everolimus, can provide promising results for more than one of the affected systems 5,7,9 . The patient's management was based on the symptoms during her hospital stay and treatment for seizure control was continued upon discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One-third of epileptic seizures in children with TSC become refractory to treatment, and it correlates with the early age at the first clinical seizure, a mutation in the TSC2 gene, and the number of cortical tubers [26].…”
Section: Introductionmentioning
confidence: 99%